Replacing target setting by value models in the 'house of quality' for value-based requirements specifications. (November 2015) - Zhang, Xinwei; Eres, Hakki; Baron, Claude; Auriol, Guillaume; Kossmann, Mario
Setting targets for engineering characteristics is common practice in the 'house of quality' for establishing requirements specifications. However, if deployed arbitrarily, this practice is prone to errors and can often yield irrational results. Three potential methodological problems have been identified, regarding the setting of independent targets for each engineering characteristic, setting fixed targets and cascading down targets from the system level to the component level have been identified. In this article, targets are categorised as constraints and goals because of their different implications for value trade-offs. Then, a 'multi-attribute utility theory' based approach is proposed, in which a system value model is developed in order to replace the setting of targets for system engineering characteristics and component value models are further derived to replace the setting of targets for component engineering characteristics. These value models enhance the traditional approach to requirements specification so that value-based requirements specifications can be developed. A case study is deployed to demonstrate the applicability of the approach in the civilian aerospace context for the development of requirements for commercial aircraft. The benefits of the proposed approach are twofold: (1) value becomes an explicit construct and (2) value can be rationally modelled and simulated in the 'house of quality' in order to establish value-based requirements specifications. Furthermore, identified methodological problems in terms of setting engineering characteristic targets at any level are mitigated.